The beneficial effect of coffee consumption in type 2 diabetes mellitus - Yusof, Nur Masyitah; May, Khin Soe (IIUM Press, International Islamic University Malaysia, 2018)
It is reported that coffee has become one of the most wildly consumed beverages in the world with the average consumption by an adult is between 3 to 6 cups per day (Van Dam and Hu, 2005). Previous studies have demonstrated that there is an inverse association between regular consumption of coffee and the risk of Type 2 diabetes mellitus (T2DM) (Rosengren et al., 2004; Paynter et al., 2006; Huxley et al., 2009; Kempf et al., 2010; Jiang et al., 2014). Based on two separate studies by Akash and colleagues, diabetes mellitus (DM) is the auto inflammatory syndrome that is associated with many abnormalities such as dyslipidaemia, beta cell function impairment, hyperglycaemia, abnormal insulin secretion and insulin resistance (Akash et al., 2012; Akash et al., 2013). If 2-h serum glucose of individuals ≥11.1 mMol L, it indicates that they are having T2DM. Many research studies have been conducted to prove the existence of an inverse relationship between the consumption of coffee and T2DM and most of them show positive results. It is suggested by some studies that there are several substances in coffee that affect the glucose metabolism, namely chlorogenic acid (CGA) and magnesium (Mg+). Coffee is also well known to be a major source of caffeine besides containing other micronutrient (van Dam et al., 2004). CGA is found in high quantities in coffee and it inhibits the glucose-6-phosphatase (G6Pase) (Arion et al., 1997; Herling et al., 1999). G6Pase is an enzyme that mostly found in the liver and kidney that will hydrolyse glucose-6 phospate before forming the glucose which being release into the blood circulation (Van & Gerin 2002). According to the overall result of previous meta-analysis on prospective studies, for every 2 cups/day increment in coffee consumption, the average incidence of T2DM was reduced by 12%. The effect on women is stronger with 15% reduction as compared to men with 8% (Jiang et al., 2014). Other than CGA, Mg+ is found in coffee also improves the effect to the glucose metabolism. One study stated that drinking 3 to 4 cups of decaffeinated coffee which has high CGA content per day will significantly decrease of the risk of T2DM by a rate of 30% (Huxley et al., 2009). Diabetes mellitus is one of the most common and a dangerous disease that occurs in Malaysia and around the world, and the number of people diagnosed with DM increases every day (Akash et al., 2013). Diet is found to play a significant role in preventing the on-set of diabetes. Considering the high consumption of coffee worldwide, its potential benefits relating to T2DM (added) and the increasing number of T2DM patients, the fact that coffee could have potential benefits is encouraging. Many prospective studies have been conducted in various countries in order to confirm the relationship between the consumption of coffee and the reduction of the risk of T2DM. Prospective study is preferable compared to cross-sectional studies, ecologic studies, and case control studies because it provides less selection bias and recall bias as well as better evidence for the causality of the event.